Nutrient composition and productivity of alternative autumn-winter forages in different sowing dates in northern Mexico - López-Jara, Anabel Guadalupe; Reta-Sánchez, David Guadalupe; Reyes-González, Arturo; Santana, Omar Iván; López-Calderón, Magali Jeaneth; Sánchez-Duarte, Juan Isidro (Revista Mexicana de Ciencias Agrícolas, 2022)
The objective of this study was to evaluate the nutrient composition and productivity of alternative forages on different sowing dates. The alternative forages were canola and safflower, and the traditional ones were barley and triticale. The four sowing dates were: November 16, December 7, December 28 and January 18, for two years. When compared with barley and triticale, canola and safflower had lower neutral detergent fiber (NDF) and higher crude protein (CP), but similar net energy for lactation (NEL). The sowing date had little impact on the nutrient composition of these forages, but the nutrient yield was significantly affected. Dry matter (DM), CP and NEL yields decreased by delaying the sowing date in all species. Canola, safflower and barley had the highest nutrient yields on November 16 and December 7, while in triticale, they occurred between November 16 and December 28. Barley and triticale produced the highest yields of DM and NEL on all sowing dates; both species showed the highest NDF yield on the first three sowing dates during the two years. In conclusion, early sowing improves the nutrient composition and productivity in canola and safflower, therefore, these crops represent a good option as an alternative forage sown in late November or early December in northern Mexico.